2014
DOI: 10.1017/s0033291714001305
|View full text |Cite
|
Sign up to set email alerts
|

A network meta-analysis on comparative efficacy and all-cause discontinuation of antimanic treatments in acute bipolar mania

Abstract: Hierarchical rank ordering by comparative efficacy and risk of all-cause discontinuations should help to guide antimanic treatment choices by clinicians, healthcare policy makers, and guideline developers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 69 publications
5
97
0
1
Order By: Relevance
“…In patients who are inadequately responsive to first‐line agents, second‐line choices include monotherapy with olanzapine (level 1), carbamazepine (level 1), ziprasidone (level 1), and haloperidol (level 1)143 or combination therapy with olanzapine plus lithium or divalproex (level 1). While each of these strategies has strong support for their efficacy, as indicated above, safety and tolerability concerns relegate them to second‐line options.…”
Section: Acute Management Of Bipolar Maniamentioning
confidence: 99%
See 2 more Smart Citations
“…In patients who are inadequately responsive to first‐line agents, second‐line choices include monotherapy with olanzapine (level 1), carbamazepine (level 1), ziprasidone (level 1), and haloperidol (level 1)143 or combination therapy with olanzapine plus lithium or divalproex (level 1). While each of these strategies has strong support for their efficacy, as indicated above, safety and tolerability concerns relegate them to second‐line options.…”
Section: Acute Management Of Bipolar Maniamentioning
confidence: 99%
“…Agents recommended as third‐line options for treatment of acute mania include monotherapy with chlorpromazine (level 2),157 monotherapy with clonazepam (level 2),158 monotherapy or adjunctive therapy with clozapine (level 4),159, 160, 161, 162 and monotherapy with tamoxifen (level 2) 143. Tamoxifen is downgraded because of the risk of uterine cancer and the lack of clinical experience despite evidence for efficacy.…”
Section: Acute Management Of Bipolar Maniamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the reference lists of review articles relevant to this topic were manually searched to identify potentially eligible papers (Arbaizar et al, 2009;Biederman et al, 2005;Brown et al, 2013;Fountoulakis et al, 2009;Fountoulakis et al, 2011;McKeage, 2014;Meduri et al, 2016;Miura et al, 2014;Perlis, 2007;Perlis et al, 2006;Scherk et al, 2007;Smith et al, 2007;Taylor, 2003;Vieta et al, 2010;Yatham et al, 2013;Yildiz et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Pharmacological therapy is often the first-line treatment for BD, followed by psychological (Oud et al, 2016) and psychosocial interventions (Goodwin et al, 2008). In addition to lithium and anticonvulsants (van der Loos et al, 2011;Yildiz et al, 2015), antipsychotic agents have also shown promising efficacy for bipolar mania (Yildiz et al, 2011) and depression (Goodwin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%